Marketing in developing countries - Kindra, G.S. (Colección de libros electrónicos de ULoyola, 2015)
The articles in this collection discuss the role of marketing in development, and include case studies from various developing countries. They consider state enterprises, marketing education, birth control and comparative marketing models.